Novel viral vectors in infectious diseases. Issue 1 (26th September 2017) - Humphreys, Ian R.; Sebastian, Sarah
Summary: Since the development of vaccinia virus as a vaccine vector in 1984, the utility of numerous viruses in vaccination strategies has been explored. In recent years, key improvements to existing vectors such as those based on adenovirus have led to significant improvements in immunogenicity and efficacy. Furthermore, exciting new vectors that exploit viruses such as cytomegalovirus (CMV) and vesicular stomatitis virus (VSV) have emerged. Herein, we summarize these recent developments in viral vector technologies, focusing on novel vectors based on CMV, VSV, measles and modified adenovirus. We discuss the potential utility of these exciting approaches in eliciting protection against infectious diseases. Abstract : A review article that summarizes recent development in viral vector‐based vaccination approaches. We consider these developments specifically in the context of exploration of these vectors in the induction of protective immunity against infectious diseases.